The overheating effects in germanium quantum well with two subbands occupied - Berkutov, I.B.; Andrievskii, V.V.; Kolesnichenko, Yu.A.; Komnik, Yu.F.; Mironov, O.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
The charge carrier overheating effect was studied in the p-type Si0.4Ge0.6/Ge/Si0.4Ge0.6 heterostructure with two subband occupy. The temperature dependences of hole-phonon relaxation time τh-ph at weak magnetic fields demonstrated transition of the 2D system from regime of “partial inelasticity” characterized by dependence τ-1h-ph ∝ T 2 to regime of small-angle scattering, described by dependence τ-1h-ph ∝ T 5 with temperature increase. But in higher magnetic fields the dependence τ-1h-ph ∝ T 3 manifests itself on dependences τh-ph(Th-ph). The possible explanations of such dependences are discussed.